Influence of adipose tissue derived mesenchymal stem cells in combination with injectable bone substitute on osteoclastogenesis in osteoporotic rats - Hanaa H. Ahmeda, Wafaa Gh. Shoushab, El-Sayed M. El-Sayed Mahdyb, Laila A. Rashedc, Sara M. Abdob (Journal of Applied Pharmaceutical Science, 2013)
The present study was designed to evaluate the influence of adipose tissue derived mesenchymal stem cell (ASCs) with or without calcium phosphate composite on osteoclastogenesis in osteoporotic rats. Mesenchymal stem cells (MSCs) were harvested from adipose tissue of both the omentum and the inguinal fat pad of male rats, as the sex mismatch, to track the MSCs fate and to ensure their homing to the injured females' femurs. The isolated ASCs were characterized via the morphological appearance, multilineage potential and the PCR detection of CD29, CD44, CD106, CD14, CD34 and CD45 surface markers. Fifty adult female albino rats were enrolled in the current study. The rats were classified into five groups: group 1 was the gonad intact control, group 2 served as untreated ovariectomized (OVX) rats, group 3 was OVX rats treated with ASCs, group 4 was OVX rats treated with ASCs with injectable bone substitute (IBS) and group 5 was OVX rats treated with IBS. The serum levels of osteoprotegerin (OPG) and receptor activator of NF-Ò›β ligand (RANKL) were assayed using ELISA procedure. In addition, nuclear factor-κβ (NF-κβ) gene expression level was estimated in femur bones using real time –PCR. The isolated ASCs proved their MSCs identity via their morphological appearance and multilineage potential. In addition, the isolated ASCs showed positive expression for CD29, CD45, CD44 as well as CD106 and negative expression for CD34 and CD14. Besides, the positive expression of the Y-chromosome (sry) gene detected in the ASCs treated groups indicated that the systemically delivered single dose of undifferentiated ASCs was able to home at the females' femur bones. Adipose tissue derived mesenchymal stem cells (ASCs) injection with or without calcium phosphate composite in OVX rats reversed the effect of ovariectomy on the studied biomarkers causing significant increase in serum OPG level accompanied with significant decrease in serum RANKL level. Also, significant down regulation of NF-κβ gene expression in femur bones was detected in the treated groups compared with untreated OVX group. These results clarified the good influence of ASCs against osteoclastogenesis. In addition the combination of ASCs injection with osteoinductive material injectable calcium phosphate composite (IBS), may be useful to achieve the significant antiosteoporotic effects.
Keywords: Ovariectomized rats, osteoclastogenesis, adipose tis